Measuring resilience in prisoners (Academic Journal of Internal Affairs, 2020)
The reintegration process is not a simple one. There are many papers about the difficulties of re-entry into society and the possible reasons of the success or the failure of reintegration. In this article, I am going to write about the role of resilience in prisoners’ reintegration process. In a brief presentation of the concept of resilience, I will introduce the models of resilience and the role of protective factors. From the several instruments that can be used to measure resilience I will highlight the most common and most empirically based scales that can be a great help to identify protective factors of incarcerated people, to make the reintegration processes more successful.
Keywords: reintegration; resilience; protective factors; risk factors